Recent Advances in Robust Superwettable Membranes for Oil–Water Separation. Issue 12 (3rd May 2019) - Lin, Xiangde; Hong, Jinkee
Abstract: Over the past decade, much progress has been made in the application of multifunctional membranes with special wettability for the separation of oil–water mixtures. This progress has been driven by frequent oil spill accidents and oily wastewater, which are enormous threats to the vulnerable aquatic environment. The design of permeable superwettable membranes for oil–water separation has been inspired by the development of highly wetting/nonwetting interfaces, but these membranes are susceptible to factors such as mechanical forces, chemical corrosion, biological fouling, and other environmental influences. Considering the complex and harsh environments that superwettable membranes must endure during the separation process, membrane durability against the loss of superwettability is critical in prolonging the life of an oil–water filtration system. Although significant advances in superwettable membranes have been made, the robustness issue remains challenging and has become a focus of many investigations. Covering nearly all publications concerning "robust, durable, usable, resistant, tolerant, or antifouling oil–water separation" published in the last five years, this work is intended as an introduction for new researchers wishing to create durable superwettable membranes for oil–water separation, as well as providing perspectives and guidance for future research in several logical directions. Abstract : Advances in superwettable membranes exhibiting high durability for robust oil –water separation are reviewed from the design of normal surfaces to permeable structures. The ability of such advanced membranes to resist harsh environments involving mechanical damage, chemical corrosion, biological fouling, and other environmental impacts is summarized. Accordingly, perspectives for future research in several directions are proposed.